Epidemiological trends in the presentation of diabetic ketoacidosis in children newly diagnosed with type 1 diabetes from 2011 to 2017 in Kuwait - Al-Abdulrazzaq, Dalia; Othman, Fouzeyah; Qabazard, Sarah; Al-Tararwa, Abeer; Ahmad, Dina; Al-Sanae, Hala; Al-Kandari, Hessa (Frontiers in Endocrinology, 2022)
Background Monitoring the trends in the presentation of T1D over decades cannot be underestimated as it provides a rich source of information on diabetes-related complications like DKA. DKA represents a medical emergency, with potentially fatal outcome, and thus the prevention of DKA is a priority in diabetes care. The aim of this study is to report on trends in the presentation of DKA in children newly diagnosed with T1D in Kuwait. Material and methods This study is based on a retrospective review of children newly diagnosed with T1D aged 14 years or less at three Governmental Hospitals representing three health sectors out of the total six health sectors in the country during the period 2011-2017. Results A total of 799 children (376 males and 423 females) were newly diagnosed with T1D. 287 children presented with DKA (35.9%) with only 73 children (9.1%) classified as severe. During the years 2011 to 2017, we note that the percentage of children older than 6 years of age presenting with severe DKA has decreased significantly (p=0.022). Unfortunately, this has not been replicated in children younger than 6 years. Conclusion This study highlights the importance of continued monitoring of clinical characteristics of children at diagnosis of T1D specifically presenting with DKA to enable diabetes care professionals to appreciate the multifaceted aspects of T1D, in particular the importance of raising awareness of the early signs of the onset of T1D with special attention to DKA and its severe consequences.